National Qualifications Framework in Practice: Problematising an Initial Teacher Education (ITE) Curriculum from a Curriculum Ergonomics Perspective - Yanda, Fikri; Khoiriyah, Khoiriyah; Thamrin, Nur Sehang; Ruminar, Hafida; Humaera, Isna (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
Claimed by some to be a successful policy tool to connect education with the industrial world, a body of research has documented issues on adapting and adopting the National Qualifications Framework (NQF), a worldwide policy phenomenon. However, there are fewer studies on implementing this framework in initial teacher education (ITE). Therefore, to fill this gap, this paper explores and contextualises the enactment of NQF within the ITE sector from a curriculum ergonomics perspective, a novice concept of analysis on the interactions between curriculum design and its use. This paper contributes to the existing research on curriculum studies, especially in the ITE sector. Implications and recommendations are also discussed.